Content-based curriculum for advanced learners - Little, Catherine A.; VanTassel-Baska, Joyce (New York, NY Routledge, Taylor & Francis Group, 2023)
"The fourth edition of Content-Based Curriculum for High-Ability Learners provides readers with a complete and up-to-date introduction to core elements of curriculum development in gifted education with implications for school-based implementation. Written by key experts in the field, this text is essential to the development of high-powered, rich, and complex curricula that treat content, process, product, and concept development considerations as equal partners in the task of educating gifted learners. Along with revised chapters, this edition contains new chapters on culturally responsive curriculum, the performing arts, robotics, and engineering design, as well as social and emotional learning. Additional material concerning talent trajectories across the lifespan accompanies a discussion of honors curriculum in higher education, rounding out this comprehensive resource. This master text is a must read for educators interested in executing effective curriculum and instructional interventions to support learning for gifted and advanced learners"--
Includes bibliographical references and index.
Keywords: Curriculum planning -- United States; Gifted children -- Education -- United States